Memoir: In Celebration of Academic and Athletic Excellence - Melville, Stephen (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
Thoughts on, and memories of, Bill Readings, curricular change, and the elements of sport.